Promoting the consumer voice in palliative care: exploring the possibility of using consumer impact statements - McConigley, Ruth; Shelby-James, T.; Currow, D. (Wiley-Blackwell Publishing Ltd., 2013)
BACKGROUND: It can be difficult to engage consumers in health decision making. This is particularly so in the area of palliative care, where consumers are very unwell and are unlikely to become involved in long-term programmes that promote consumer input. This paper explores the possibility of using ‘Consumer Impact Statements’ to facilitate the inclusion of the viewpoint of people at the end of life in the process of policy and decision making, particularly in the area of subsidy of pharmaceuticals used in palliative care. SEARCH STRATEGY: A broad search was conducted to find information about the use of impact statements in any health field. The health literature and grey literature were searched to explore the use of Consumer Impact Statements to date. RESULTS: No papers were found describing the use of Consumer Impact Statements in the palliative care setting. Health impact assessment is used in the areas of environmental health and community health. Impact statements are less commonly used in other areas of health, especially policy development, and no formal description of a Consumer Impact Statement was found. DISCUSSION: There is considerable scope for developing the use of Consumer Impact Statements to promote the consumer viewpoint in health decision making, because it will allow people who are otherwise unlikely to contribute to the public debate to have their views heard by decision makers. CONCLUSION: The use of Consumer Impact Statements is particularly suited to palliative care, given that consumers are often otherwise unable to contribute to the public debate.